Combined intra- and extra-endoscopic techniques for endoscopic intraventricular surgery with a new mini-tubular port - Liu, Xi; Qiu, Yan'kai; Zhang, Fan; Wei, Xiaoming; Zhou, Zhisong; Zhang, Feng; Xue, Yiteng; Ma, Zhaoru; Wang, Xiaosong; Shen, Hong; Lin, Zhiguo; Shi, Huaizhang; et al. (Frontiers in Surgery, 2022)
Objective: Intraoperative hemorrhage is the greatest fear in the endoscopic intraventricular surgery. There are very few published methods of hemostasis during the conventional endoscopic intraventricular surgery. We design a new mini-tubular port to combine intra- and extra- endoscopic techniques for endoscopic intraventricular surgery, in which some techniques can be done more efficiently for control bleeding and complicated procedures. Methods: The mini-tubular port consists of an outer sheath and an obturator. The sheath is thin-walled transparent cylinder with sheath thickness of 0.35mm, which is 10 mm in diameter and 90mm in length. 36 patients were suffered from endoscopic intraventricular surgery by the mini-tubular port. Results:The patients ranged from 0 to 72 years of age (mean, 38years),19 men and 17 women. Pure ETV was performed in 20 cases, pure biopsy was performed in 2 cases. ETV and biopsy was performed in 5 cases, ETV and removal of the cysticerci was performed in 5 cases, cyst fenestration was performed in 1 case, ETV and cyst fenestration was performed in 2 cases, and ETV and shunt removal was performed in 1 case. Two patients received the microscopic surgery following the endoscopic surgery at the same time. A total of 17 patients (47%) underwent extra-endoscopic technique. The median Karnofsky Performance Status (KPS) score of the patients before surgery was 50, and the median KPS score of the patients after one month of surgery was 80. Through Wilcoxon test, the difference of the patients' KPS score before surgery and after one month of surgery was statistical significance. There were 27 patients whose KPS scores were≥70. the rate of favorable prognosis after one month of surgery was 75%. There was no seizure in all patients. Conclusions: Mini-tubular port is convenient to combine intra- and extra- endoscopic techniques for endoscopic intraventricular surgery. Application of these techniques can efficiently control bleeding during operation and improve the confidence of surgeons, at the same time improve the efficiency of doing some complicated procedures.